A promising way to open an energy gap in bilayer graphene. Issue 40 (30th September 2015) - Hao, Jialei; Huang, Chengxi; Wu, Haiping; Qiu, Yuhao; Gao, Qian; Hu, Zhenpeng; Kan, Erjun; Zhang, Lixin
Abstract : Sandwiching BLG between two polarized substrates, we enhance the coupling between BLG and open an energy gap. Abstract : There has been huge research interest in the energy gap problem of monolayer and bilayer graphene due to their great potential in practical applications. Herein, based on first-principles calculations, we report a promising way to open a large band gap in bilayer graphene (BLG) by sandwiching it between two substrates, although this is not usually expected to occur due to the weak interlayer interactions dominated by van der Waals forces. Taking surface-functionalized boron–nitrides as substrates, we predict from first-principles calculations that BLG can have energy gaps ranging from 0.35 eV to 0.55 eV, depending on the substrates and stacking order. Compared to other methods of band-gap manipulation in BLG, the structural integrity of BLG is well-preserved in our study, and the predicted energy gap is suitable for electric devices. Since the proposed method is easily realized in experiments, our results will hopefully accelerate the application of graphene in semiconductor devices and promote the development of graphene technology.